2011
DOI: 10.1007/s11663-011-9485-6
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Evolution of Atomized Al-0.61 wt pct Fe and Al-1.90 wt pct Fe Alloys

Abstract: The microstructure evolution of impulse atomized powders of Al-0.61 wt pct and Al-1.90 wt pct Fe compositions have been investigated with a scanning electron microscope, transmission electron microscope, neutron diffraction, and backscattering electron diffraction (EBSD). Both hypoeutectic and hypereutectic compositions demonstrated similar macrostructure (i.e., primary a-Al dendrites/cells with eutectic Al-Fe intermetallics decorated at the dendritic/cellular walls). Selected area electron diffraction (SAED) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Indeed, a much more likely explanation is that there is little movement of fragments following remelting and that the dominant tendency is not to nucleate new grains but instead to be incorporated into existing growing grains with a small orientation mismatch. The small misorientations giving rise to such incorporation in to larger grains would be consistent with the results obtained for Al-Fe alloys by [24].…”
Section: Relationship Between Dendrite Fragmentation and Grain Refinesupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, a much more likely explanation is that there is little movement of fragments following remelting and that the dominant tendency is not to nucleate new grains but instead to be incorporated into existing growing grains with a small orientation mismatch. The small misorientations giving rise to such incorporation in to larger grains would be consistent with the results obtained for Al-Fe alloys by [24].…”
Section: Relationship Between Dendrite Fragmentation and Grain Refinesupporting
confidence: 90%
“…Heringer et al [23] predicted that remelting should occur in Al-based alloys, with the extent of remelting increasing as the melt undercooling increased. EBSD analysis appeared to confirm remelting and detachment of secondary arms, which displayed a slight misorientation with respect to the primary dendritic trunks [24] . Peng et al [25] observed clear evidence of the remelting and fragmentation of secondary dendrite arms in as-solidified Sn-36at.% Ni alloy, with many of the secondary arms becoming detached from their parent trunks and subsequently partially spheroidized (see e.g.…”
Section: Introductionmentioning
confidence: 93%
“…The peaks at 2Θ 18.166°, 20.815°, 23.908° and 27.306° confirm the presence of XRD was performed on three select samples (Figure 7). Sample AlFe1.1-0 was analyzed in order to confirm the presence of the Al 6 Fe metastable phase because of non-equilibrium solidification, whereas the AlFe1.1-4 and AlFe1.1-24 samples were analyzed to confirm the transformation of the Al 6 Fe metastable phase into the stable Al 13…”
Section: Resultsmentioning
confidence: 99%
“…Iron (Fe) is one of the most harmful impurities in most commercial aluminium alloys and is usually limited to 0.05 mass/%. Fe is present in almost all aluminium alloys because it can be introduced into the alloys during electrolysis from ores, through interaction with the furnace lining and fluxes, or simply by dissolving foundry equipment during casting, but most Fe impurities contamination usually occurs during recycling [1][2][3]. Fe-rich intermetallic phases are often associated with lower mechanical properties [4,5], but on the other hand Fe is used as an alloying element in some wrought aluminium alloys used in rolling because of its suitable ductility and strength combination at thinner gauges, when small amounts of Si are added [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The result of non-equilibrium solidification in the Al-Fe alloy system is the formation of various metastable intermetallic phases, the most common of which are Al 6 Fe, Al x Fe and Al m Fe [3,[17][18][19][20]. During a homogenization heat treatment, the transformation of metastable into stable phases takes place.…”
Section: Introductionmentioning
confidence: 99%